THE LEVEL OF KNOWLEDGE AND SKILLS OF ARBITRATION IN FOOTBALL FOR HALLS FOR TEACHERS AND TEACHERS OF PHYSICAL EDUCATION IN SCHOOL TOURNAMENT - Ahmed Zghair Idan Al-Hilali (Scholars Digest Publishing, 2025)
This study aimed to identify the level of refereeing knowledge and skills in futsal among physical education teachers involved in school tournaments. The researcher used the descriptive survey method, and the study sample consisted of 60 male teachers from public schools who participated in refereeing school futsal competitions. A specially designed questionnaire was used, covering two main areas: refereeing knowledge and practical refereeing skills. After verifying its validity and reliability, data were collected and statistically analyzed. The results showed that the participants possessed a good level of refereeing knowledge and a moderate to good level of practical skills, with statistically significant differences based on experience and academic qualification. The study recommended implementing continuous training programs to enhance the refereeing competence of physical education teachers.
Keywords: Refereeing, Futsal, Refereeing Knowledge, Skills, School Tournaments, Physical Education Teachers.